INPLANE RESISTIVITY IN GRAPHITE-INTERCALATION COMPOUNDS OBTAINED FROM CONDUCTION-ELECTRON-SPIN-RESONANCE MEASUREMENTS - Walmsley, L. (American Physical Soc, 1992)
We developed a procedure to take advantage of the magnetic-field-modulation-frequency effect on the line shape of conduction-electron-spin resonance of graphite intercalation compounds (GIC's) to extract the absolute value of the in-plane resistivity. We calculated the power absorbed in each slice of the sample normal to the wave penetration, multiplied by a factor to account for the magnetic-field-modulation-frequency effect. Room-temperature spectra of stage-I AlCl3-intercalated GIC in both H-0 perpendicular-to c and H-0 parallel-to c configurations were fitted to the theoretical line shapes and the value of in-plane resistivity (and also the value of c-axis resistivity) obtained from the fitting parameters are in reasonable agreement with those from the literature.